The Effectiveness of Local Wisdom-Based Monopoly Games in Teaching Friendship in Diversity in Indonesian Language Education - Candani, Ni Wayan Cintya; Kristiantari, Maria Goreti Rini; Sujana, I Wayan (Universitas Pendidikan Ganesha, 2024)
Problems in Indonesian language learning in second-grade elementary school often relate to students' lack of engagement in understanding the material in a fun and relevant way. This study aims to analyze the effectiveness of a local wisdom-based Monopoly game in teaching the topic of friendship in the context of diversity in Indonesian language learning for second-grade students. This research is a development study that uses the ADDIE model. The subjects of the study were 32 second-grade students. Data collection methods and instruments included multiple-choice objective tests and questionnaires. Data analysis techniques involved both descriptive and inferential quantitative statistics. The results of the study indicate that the local wisdom-based Monopoly game is considered suitable for use in learning. Furthermore, the effectiveness test results showed that tcalculated > ttable, thus rejecting H₀ and accepting H₁. This indicates that the local wisdom-based Monopoly game is effectively applied in teaching Indonesian language on the topic of friendship in diversity for second-grade students. The conclusion of this study is that the implementation of a local wisdom-based Monopoly game can improve the effectiveness of Indonesian language learning, particularly on the topic of friendship in diversity, in a more enjoyable and relevant way for students.